Antithymocyte Globulin as Second-Line Therapy in Graves Orbitopathy—Preliminary Results From a Prospective Single-Center Study - Sarnat-Kucharczyk, Monika; Świerkot, Maria; Handzlik, Gabriela; Kulawik, Grażyna; Jagoda, Krystyna; Grochoła-Małecka, Iga; Fryżewska, Joanna; Mrukwa-Kominek, Ewa; Chudek, Jerzy (Frontiers in Endocrinology, 2022)
Objective: Management of Graves' orbitopathy remains a challenge. Our previous case report has shown promising results for rabbit anti-thymocyte globulin (rATG) in the treatment of Graves' orbitopathy. Design: We present the response of 7 individuals with active moderate-to-severe steroid-resistant Graves' orbitopathy to rATG, representing preliminary results from a prospective single-centre study. Methods: rATG was administered intravenously at a dose of 0.8 – 1.0 mg/kg daily (cumulative dose of 150-200 mg). The primary outcome measures at weeks 24 and 48 were ≥ 2 point reduction in Clinical Activity Score from baseline, a proptosis response, a diplopia response, and improvement of distant best-corrected visual acuity and mean retinal sensitivity. Key secondary outcomes included stabilization of ganglion cell complex thickness, a decrease of retinal nerve fibre layer in OCT, and reduction in CD4/CD8 ratio and TRAb at 48 weeks. Results: An improvement in clinical activity score was observed in all patients, with disease inactivation in 3 cases. Proptosis reduction equal or greater than 2 mm was noted for 8 of 10 eyes. Diplopia improved in three of 6 patients. There was an improvement in best-corrected visual acuity (from 0.69 to 0.78) and mean retinal sensitivity (from 20.8 dB to 23.5 dB). In addition, there was a long-lasting improvement in CD4/CD8 ratio in 6 patients. Two patients experienced adverse events (influenza and serum sickness). Conclusion: rATG therapy offers long-lasting improvement in moderate-to-severe steroid-resistant Graves' orbitopathy with improvement in functional vision (reduction of diplopia, improvement of visual acuity, retinal sensitivity, and VEP pattern). The therapy is well-tolerated.